Canadian annual review of politics and public affairs, 1985 - Byers, R. B. (Book collections on Project MUSE., 1988)
The Canadian Annual Review has become an indispensable reference book for those concerned directly or indirectly with Canadian public affairs.Compiled by a corps of Canadian scholars and experts, It offers both a concise, convenient record of the year's events and a responsible appraisal of important developments.Among the events of 1985 analysed in this volume are the activation of the free trade talks with the United States, adding a note of tension to the relationship that in March was serenaded at the Shamrock Summit. In Ontario the forty-year Tory dynasty was ended by an agreement between David Peterson's Liberals and the New Democratic Party. Across the country, relations between the federal and provincial governments improved considerably, in the aftermath of the Mulroney victory in the previous year.